Muslim Cultures of the Indian Ocean Diversity and Pluralism, Past and Present - Pradines, Stephane; Topan, Farouk (Edinburgh University Press, 2023)
This book examines the role of Muslim communities in the emergence of connections and mobilities across the Indian Ocean World from a longue durée perspective. Spanning the 7th century through the medieval period until the present day, this book aims to move beyond the usual focus on geographical sub-regions to highlight different aspects of interconnectivity in relation to Islam. Analysing textual and material evidence, contributors examine identities and diasporas, manuscripts and literature, as well as vernacular and religious architecture. It aims to explore networks and circulations of peoples, ideas and ideologies, as well as art, culture, religion and heritage. It focuses on global interactions as well as local agencies in context.